INDUKSI PERKECAMBAHAN BIJI SIRSAK ( Annona muricata ) MENGGUNAKAN AIR KELAPA MUDA - Andriani, Andriani; Advinda, Linda; Novi, Novi (Pendidikan Biologi, 2013)
ABSTRACTAnnona muricata L. is a kind of plant growing and fruiting perennially if the water  demond  is  apparently  sufficed.  A.  muricata  L.  seed  has  averagely  less germination power, however it can be improved by the induction. Coconut water is proved to induct that power because it contains some essences supporting seed growth: auxin, gibberellind and cytokinins. This research was carried out at 13rd January until25th   February in Physiology Laboratory of Biology Departement Unversity of Padang.This is a descriptive research which used six concentrates of coconut water are: 0%,20%, 40%, 60%, 80% and 100% with every concentrate is put on four plastic scuttles. The observation was held six week to find out days when seed started growing and amount of seed germinating. The result showed that germination in 60% appeared in19th      day.  The  writer  summarizes  that  coconut  water  dad  not  be  able  to  inductgermination of A. muricata seed. The result evidenced that from 120 seeds germination, there werw only 7 seeds started growing.